Хоминг как метод экспериментального изучения птиц - Кистяковский, А.Б.; Суходольская, Н.К. (Вестник зоологии, 1974)
Neighbouring homing is a delivery of birds to such distances from which they can come back the same day without spending a night and time for rest and feeding. Usually it is a distance to 100 km. The dependence of orientation on weather conditions, distance and direction of delivery, training and age of birds, stages of nest life, etc. was studied by means of experiments on neighbouring homing. Combination of homing with radiotracing is very promissing. In certain experiments of homing the circular cages are used.